Peran Akupunktur sebagai Terapi Penunjang untuk Fibrilasi Atrium - Ayu Permata Sari (Unram Medical Journal, 2022)
Atrium fibrillation (AF) is a common tachyarrhythmia and its prevalence increases with age. AF causes increased morbidity and mortality, including stroke, heart failure and decreased quality of life. The current treatment for AF has pro-arrhythmic side effects, procedurally expensive and complex, invasive procedures have a low success rate, high costs and long-term consumption of antiarrhythmic drugs can damage other organs outside the heart. Acupuncture is a method that is widely studied for cardiac arrhythmia problems, such as atrium fibrillation. Acupuncture works by stimulating autonomic nerves, decreasing sympathetic and vagal activity, thereby decreasing AF induction in the heart. Furthermore, acupuncture therapy compared with the anti-arrhythmic drug amiodarone was not more beneficial in the long term, but with acupuncture there were fewer side effects. Recent studies have also tried auricular acupuncture which is a branch of the vagal nerve and as the result the heart rhythm changes immediately to sinus rhythm, without cardioversion, either pharmacological or electrical. Therefore, acupuncture deserves to be considered as an alternative therapy option for patients with atrium fibrillation. Keywords : acupuncture, atrium fibrillation, cardiac arrhythmia, cardioversion